Poly(2-ethyl-2-oxazoline-co-ethyleneimine)-block-poly(ε-caprolactone) based micelles: synthesis, characterization, peptide conjugation and cytotoxic activity. (28th July 2021) - Gulyuz, Sevgi; Ozkose, Umut Ugur; Parlak Khalily, Melek; Kesici, Mehmet Seckin; Kocak, Polen; Bolat, Zeynep Busra; Kara, Asli; Ozturk, Naile; Özçubukçu, Salih; Bozkir, Asuman; Alpturk, Onur; Telci, Dilek; et al.
Abstract : Here we present self-assembled polymeric micelles as potential delivery systems for therapeutic agents with highly tunable properties. Abstract : Here we present self-assembled polymeric micelles as potential delivery systems for therapeutic agents with highly tunable properties. The major goal of this study is to design breast and prostate cancer specific targeting peptide modified PEtOx- co -PEI- b -PCL block copolymer based micelles as a targetable carrier system in cancer treatment. For this, a series of micelles based on poly(2-ethyl-2-oxazoline)- co -polyethyleneimine- block -poly(ε-caprolactone) [P(EtOx- co -EI)- b -PCL] copolymers with two different proportions of PEI (30% and 60% hydrolysis degrees of PEtOx) were successfully prepared. The block copolymers were synthesized using a combination of living cationic ring-opening polymerization and a copper(i )-catalyzed azide–alkyne cycloaddition (CuAAC) click reaction. Then, peptide 18 and peptide 563 were conjugated to P(EtOx- co -EI)- b -PCL through a thiol–ene click-type reaction to obtain the desired tumor-targeting. The structural properties of the copolymers were confirmed by 1 H NMR, FT-IR, UV-Vis spectrometry and GPC. Peptide and non-peptide-conjugated micelles with particle sizes between 82 ± 0.6 and 170 ± 10.7 nm were obtained by self-assembly with two different chain lengths of PEI blocks. The micelles containing the 60% PEI block showed increased zeta potential values. The cytotoxicity of the copolymers was evaluated under in vitro conditions. Overall, our results indicate that the micelles prepared with peptide-conjugated block copolymers can be used as potential nanocarriers for targeted therapeutic delivery systems.